(untitled) (Iranian Journal of Kidney Diseases, 2022)
Familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC) is a rare autosomal recessive disorder that is characterized by renal magnesium wasting, hypercalciuria and eventually kidney failure which mostly affects children and young aged adults. Mutation of genes of claudin-16 and claudin-19 are involved in the pathogenesis of this disorder, which leads to renal magnesium and calcium wasting. A 35-year-old man with end-stage kidney disease (ESKD) was referred to our clinic due to bilateral nephrocalcinosis, detected by ultrasonographic study, for further evaluation. Detailed investigations revealed that his siblings had also similar presentations of hypomagnesemia, hypercalciuria, nephrocalcinosis and chronic kidney disease (CKD). Sanger sequencing showed a novel mutation (c.338G > A: p.C113Y) at the second exon of the CLDN16 gene. The patient underwent kidney transplantation and his siblings received only medical treatment. In young patients with ESKD and concomitant nephrocalcinosis, especially where there is a family history of CKD/ESKD, genetic evaluation is strongly recommended. DOI: 10.52547/ijkd.6845